Feedback-based bandwidth allocation with call admission control for providing delay guarantees in IEEE 802.11e networks - G. Boggia; P. Camarda; L.A. Grieco; S. Mascolo (Computer Communications, 2005)
The 802.11e working group has recently proposed innovative functionalities in order to support delay-sensitive multimedia applications, such as real-time voice and video, in Wireless Local Area Networks (WLANs). In particular, the 802.11e proposal introduces: (1) the Hybrid Coordination Function (HCF), which is an improved channel access method aimed at allocating the first-hop WLAN bandwidth to delay-insensitive and delay-sensitive flows; (2) a Call Admission Control (CAC) algorithm for preventing network overloads, which would drastically degrade the service offered by the network; (3) and a Signalling scheme for service request and QoS service level negotiation. This paper proposes a dynamic bandwidth allocation algorithm along with a measurement-based CAC algorithm for providing delay guarantees to real-time media flows in IEEE 802.11e networks. The dynamic bandwidth allocation algorithm has been designed using classic feedback control; whereas the CAC scheme is an extension of the one proposed by the 802.11e working group because it takes into account the actually used resources rather than the average rates declared by data sources. Both the schemes exploit the HCF Controlled Channel Access (HCCA) centralized access method. The proposed algorithms have been implemented in the ns-2 simulator and extensive computer simulations have been carried out to assess their validity. Simulation results have shown that proposed algorithms protect the WLAN from heavy overloads and guarantees bounded delays for multimedia flows, whereas, analogous algorithms proposed by the 802.11e working group fail for high network loads.
QoFIS 2003
Keywords: Quality of service; Wireless LAN; Dynamic bandwidth allocation; Feedback control